Gambaran Pemenuhan Personal Hygiene Mahasiswa Tingkat I, II dan III di Kota Tangerang Banten. - Silaban, Merri; Sartika, Ikah (Jurnal Kesehatan Holistic, 2024)
Background: Personal hygiene is one of the things that determines health status consciously in maintaining health and preventing diseases, especially disorders of the skin. Personal hygiene is very much needed and important in everyday life, especially as a student. A student is someone who is in the process of gaining knowledge or studying and is registered to be undergoing education at one of the universities. Objective: To know the Picture of Personal Hygiene Fulfillment of Level I, II and III Students in Tangerang City, Banten. Methods: The research used is descriptive research. Results: The results showed that 98.2% of treatments were in the clean category, nail and foot care in the net category of 93% of respondents. The hair care category 82.5% of respondents were in the clean category, dental and oral care 91.2 respondents were in the unclean category, ear and nose care 75.4% were in the clean category, the dressing category 70.2% of respondents were in the unclean category. Conclusions: The personal hygiene of respondents on Nail and Foot Care Skin Care, Hair Care, Ear and Nose Care Most of the respondents were in the good category, this was influenced because Most respondents began to understand how important it is to pay attention to personal hygiene. While the personal hygiene of respondents in doing Dental and Oral Care and Dressing, Mostly in the category of lacking, this can increase the risk of health problems in respondents, so personal hygiene in respondents related to Dental and Oral Care and Dressing must be improved again.